RITUAL LANDSCAPE AND ASTRONOMICAL MARKERS IN THE SITE UÑA TAMBO, NEVADOS DE CACHI, SALTA, ARGENTINA - Jacob, Cristian (2013)
In this paper we will realize the new research in the Nevados de Cachi, Salta, Argentina by focusing on the site that we called Uña Tambo, and what was its integration within the network of Inka sites in the region. We’ll concentrate on some aspects of the settlement archaeoastronomical, without neglecting the visual and symbolic importance of the location in that kind of sites as well as their relevance within Inka rituals related to water, agriculture and the cult of Apus.